Superficial eaudiobook More adventures from the andy cohen diaries. - Cohen, Andy (Macmillan Audio, 2016)
The star-studded and sidesplitting follow up to The Andy Cohen Diaries. This program is read by the author. The megapopular host of Watch What Happens: Live and executive producer of The Real Housewives franchise is back, better than ever, and telling stories that will keep his publicist up at night. Since the publication of his last book, Andy has toured the country with his sidekick Anderson Cooper, hit the radio waves with his own Sirius station, Radio Andy , appeared on Real Time with Bill Maher despite his mother's conviction he was not intellectually prepared, hosted NBC's Primetime New Year's Eve special, guest edited Entertainment Weekly , starred in Bravo's Then & Now with Andy Cohen, offended celebrities with his ongoing case of foot-in-mouth disease, and welcomed home Teresa "Namaste" Giudice, from a brief stint in jail. Hopping from the Hamptons to the Manhattan dating world, the dog park to the red carpet, Cardinals superfan and mama's boy Andy Cohen, with Wacha in tow, is the kind of star that fans are dying to be friends with. This book gives them that chance. If The Andy Cohen Diaries was deemed "the literary equivalent of a Fresca and tequila" by Jimmy Fallon, Superficial is a double: dishier, juicier, and friskier. In this account of his escapades—personal, professional, and behind-the-scenes—Andy tells us not only what goes down, but exactly what he thinks of it. "Because of his recognizable voice, this audiobook is the best format to hear Cohen's gossip on pop culture and how he worked his way up in the entertainment industry. Best of all, he laughs and enjoys his own stories right along with you." —Audiofile on Most Talkative